2022
DOI: 10.1021/acs.langmuir.2c00710
|View full text |Cite
|
Sign up to set email alerts
|

Control of Tyrosyl Radical Stabilization by {SiO2@Oligopeptide} Hybrid Biomimetic Materials

Abstract: Tyrosine radicals are notoriously short-lived/unstable in solution, while they present an impressive degree of stability and versatility in bioenzymes. Herein, we have developed a library of hybrid biomimetic materials (HBMs), which consists of tyrosine-containing oligopeptides covalently grafted on SiO 2 nanoparticles, and studied the formation, lifetime, and redox properties of tyrosyl radicals. Using electron paramagnetic resonance spectroscopy, we have studied the radical-spin distribution as a probe of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…On the other hand, when tyrosine was intercalated in laponite clay, [30] the g‐value (g=2.0041) and 1 H‐hyperfine splitting were closed to free‐tyrosine radical in solution. Furthermore, we have recently demonstrated that incorporation of the tyrosine‐radical in an oligopeptide grafted on SiO 2 nanoparticles [31] retains the free‐tyrosine radical spin distribution. Taken in account this information, it is concluded that: [i] when tyrosine radicals are grafted on carbon matrices for example, carbon‐nanotubes, [33] graphene or GO, the spin of the radical tends to delocalize over the carbon matrix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, when tyrosine was intercalated in laponite clay, [30] the g‐value (g=2.0041) and 1 H‐hyperfine splitting were closed to free‐tyrosine radical in solution. Furthermore, we have recently demonstrated that incorporation of the tyrosine‐radical in an oligopeptide grafted on SiO 2 nanoparticles [31] retains the free‐tyrosine radical spin distribution. Taken in account this information, it is concluded that: [i] when tyrosine radicals are grafted on carbon matrices for example, carbon‐nanotubes, [33] graphene or GO, the spin of the radical tends to delocalize over the carbon matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H‐hyprefine couplings are smaller than that of free‐tyrosine radical in solution, which agrees with less‐spin on the phenoxy‐ring. [ii] when the tyrosine radicals are not‐grafted i. e., simply intercalated in a solid‐matrix for example, such as a clay, [30] or incorporated in oligopeptides, [31] then the radical resembles free‐tyrosine radical in solution. Association of the tyrosine‐radical with the carbon matrix seems to be related with preference to diffuse the radical over the carbon‐matrix, as it has been observed originally in the case of carbon‐nanotubes [33] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We justify the choice of material, using silica nanoparticles in an effort to control the 1 O 2 reaction. Somewhat similarly, control of radical stabilization and photochemical reactions have been obtained on silica nanoparticles. We propose that our 1 O 2 air–solid method could have general applicability in a variety of research areas, such as interfacial 1 O 2 photoimaging , and environmental chemistry. , Therefore, we provide a detailed description of SIM, which enables one to gauge Pr/ 1 O 2 adduct binding. This includes how to conduct the airborne and surface-associated 1 O 2 lifetime experiments, while differentiating how 1 O 2 plays important roles in oxidizing particulates with intermediacy on surfaces , and in air. , …”
Section: Introductionmentioning
confidence: 83%
“…According to Table 1 , among the most common oxygen-centered free radicals, namely radical species where the unpaired electron is located in the oxygen atom, are the hydroxyl radicals ( • OH) [ 64 ], the superoxide anion radicals ( • O 2 − ) [ 64 ], the hydroperoxyl (HO 2 • ) radical [ 64 ], the alkoxyl (RO • )[ 64 , 67 ], and peroxyl radical (ROO • ) [ 64 ], lipid alkoxyl (LO • )[ 64 , 67 ] and lipid peroxyl (LOO • ) radicals [ 64 ], semiquinone (SQ •− ) [ 68 ] radicals, and carbonate (CO 3 •− ) radicals [ 69 , 70 ]. Similarly to alkoxyl radicals, phenoxyl radicals (e.g., tyrosyl radical, Tyr • ) are common, especially in biological systems [ 71 , 72 ]. Moreover, sulfate radicals (SO 4 ●− ) [ 73 ] are generated via the activation of persulfates, such as peroxydisulfate (PDS, S 2 O 8 2− ) and permonosulfate (PMS, HSO 5 − ), characterized by the presence of an O–O bond (similar to hydrogen peroxide) [ 74 ].…”
Section: Oxidant Species and Counterbalancing Antioxidant Mechanismsmentioning
confidence: 99%